Implementasi Aplikasi Exambro Sebagai Pengawasan Penilaian Hasil Belajar Peserta Didik di SMA Negeri 1 Wangon - Yosi Intan Pandini Gunawan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research illustrates how the internet has provided unlimited access to vast educational and information resources. Educators and Learners can access learning materials, scientific journals, textbooks, and other online resources relevant to the learning topic. This eliminates geographical limitations and allows schools with limited resources to acquire quality learning materials. This study aims to determine the implementation of the exambro application as a supervision of the assessment of student learning outcomes at SMA Negeri 1 Wangon. Through the Exambro Application implemented at Wangon State High School, it can be an application to supervise students in the process of assessing learning outcomes. The type of research used is qualitative descriptive. The instruments used are observation and interviews. The results showed that this Exambro application can minimize cheating on students. The use of the Exambro application has advantages, but there are still disadvantages in the process of using it. That way educators must carefully prepare this application before sharing it with students. To create good internet utilization through this exambro application in supervising the assessment of student learning outcomes at Wangon State High School